2005
DOI: 10.1002/ijfe.257
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric adjustment and nonlinear dynamics in real exchange rates

Abstract: This paper examines whether deviations from PPP are stationary in the presence of nonlinearity, and whether the adjustment towards PPP is symmetric from above and below. Using alternative nonlinear models, our results support mean reversion and asymmetric adjustment dynamics. We find differences in magnitudes, frequencies and durations of the deviations of exchange rates from fixed and time-varying thresholds, both between over-appreciations and over-depreciations and between developed and developing countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 81 publications
1
13
2
Order By: Relevance
“…Empirical application of a TAR model (Obstfeld and Taylor, 1997;Chowdhury, 2004, Leon andNajarian, 2005), provides support for the theory of discrete adjustments towards the PPP equilibrium and, thus, o¤ers evidence in favour of the PPP.…”
Section: Real Exchange Rate Issues and Related Literaturementioning
confidence: 85%
See 1 more Smart Citation
“…Empirical application of a TAR model (Obstfeld and Taylor, 1997;Chowdhury, 2004, Leon andNajarian, 2005), provides support for the theory of discrete adjustments towards the PPP equilibrium and, thus, o¤ers evidence in favour of the PPP.…”
Section: Real Exchange Rate Issues and Related Literaturementioning
confidence: 85%
“…These tests would typically result from regime switching models, where the RER is allowed to display di¤erent behaviour and, therefore, assume di¤erent speeds of adjustment at the di¤erent states. Several models were competing for the choice of the "correct" switching function, based on theoretical considerations about the nature of forces driving the RER behaviour (Leon and Najarian, 2005).…”
Section: Real Exchange Rate Issues and Related Literaturementioning
confidence: 99%
“…The work of Michael, Nobay and Peel (1997), Peel, Sarno and Taylor (2001), Bec, Carrasco and Salem (2004), and Leon and Najarian (2005) indicated that a three regime TAR better describes the stochastic process followed by several RER, corroborating the transaction cost theory. An important difference between the work of Leon and Najarian resides on the fact that they do not impose symmetric thresholds, which they found to be an important restriction.…”
Section: Evidences On the Behavior Of The Real Exchange Ratementioning
confidence: 60%
“…This last finding goes in the direction of the results obtained with the use of TAR family of models but it does not necessarily validate the use of symmetric thresholds so commonly employed in previous studies. Our analysis actually gives more support to non symmetric TAR models as implemented by Leon and Najarian (2005).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation